Kromong Pacet River Water Quality, Mojokerto Based on the Plankton Diversity Index - Uhibbulloh, Nur Ibnu; Purnomo, Tarzan (LenteraBio : Berkala Ilmiah Biologi, 2025)
The Kromong river is one of rivers in Pacet Mojokerto tourist area. The Kromong river is used by residents for bathing, washing, agricultural irrigation, rafting or rafting as a tourist attraction, and sand mining. Various human activities could enable changes in the physical and chemical factors of waters which directly affect the diversity of aquatic biota, especially plankton. The quality of a body of water can be determined from the plankton diversity index. The objectives of this research were to determine the watered quality in the Kromong Pacet River, Mojokerto based on the plankton diversity index. Sampling was carried out at 3 different stations; plankton identification was carried out at the ecology laboratory. The plankton diversity index was calculated by using the Shannon-Wiener diversity index formula. The research results showed that plankton diversity in the Kromong Pacet River, Mojokerto consists of 11 divisions, 22 families, 24 genera, the plankton diversity index was 3.02479, including unpolluted conditions. Water quality shows that all criteria met quality standards with an average of 36. 44 mg/l and 3. 10 ppm.